2015
DOI: 10.4274/turkderm.79989
|View full text |Cite
|
Sign up to set email alerts
|

Positivity of autologous serum skin test in patients with alopecia areata and vitiligo and in healthy individuals

Abstract: Background and Design: Autologous serum skin test (ASST), the best in-vivo test displaying in vitro basophil histamin releasing activity, is used in the diagnosis of chronic autoimmune urticaria. Besides, it is cheap and is easy to perform. It has been found that in ASST-positive chronic urticaria patients, autoimmune thyroid disease especially and other autoimmune diseases were more common and the level of autoimmune markers were higher compared to others. Autoimmunity is accused in the pathogenesis of alopec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Actually, it has been known that ASST is not specific for CSU. For example, Güven et al found ASST positivity in patients with alopecia and vitiligo [10]. Its sensitivity and specificity was reported as approximately 70-80% [11].…”
Section: Reliability Of Asstmentioning
confidence: 99%
“…Actually, it has been known that ASST is not specific for CSU. For example, Güven et al found ASST positivity in patients with alopecia and vitiligo [10]. Its sensitivity and specificity was reported as approximately 70-80% [11].…”
Section: Reliability Of Asstmentioning
confidence: 99%